Deep Learning Approach (Mindful, Joyful, and Meaningful Learning) in Elementary School Science Education: A Systematic Literature Review - Anggit Grahito Wicaksono; Jumanto Jumanto; Viera Nur Khalifah (MIMBAR PGSD Undiksha, 2026)
Science education in Indonesia faces fundamental challenges, as evidenced by the 2018 PISA results which ranked the country 70th out of 79 nations. This situation indicates the urgent need for innovative pedagogical approaches to overcome the limitations of conventional teaching methods. This study aims to analyze the implementation and impact of integrating the Deep Learning approach comprising Mindful, Joyful, and Meaningful Learning in elementary school science education. The research employed a systematic literature review (SLR) methodology following the PRISMA protocol, analyzing 16 articles published between 2020 and 2025 sourced from Google Scholar, Scopus, ERIC, and SpringerLink databases. The findings reveal that effective implementation follows a sequential and synergistic strategy: Mindful Learning establishes cognitive readiness through mindfulness practices and metacognitive reflection; Joyful Learning enhances emotional engagement through gamification and interactive activities; while Meaningful Learning ensures contextual relevance through problem-based and project-based learning. The impact of this integration is multidimensional in nature, encompassing significant improvements in students' conceptual understanding, strengthening of critical thinking skills, enhancement of learning motivation, and development of socio-emotional competencies including collaboration and self-regulation abilities. The study concludes that the integration of these three approaches creates a transformative and holistic pedagogical framework for revitalizing elementary science education. The general implications of these findings provide a conceptual foundation for developing more meaningful learning practices and serve as a reference for formulating educational policies oriented toward sustainable improvement of science learning quality.